UPAYA MENINGKATKAN PROSES HASIL BELAJAR KOGNITIF SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN IPAS DI KELAS IV SDN 101883 LIMAU MANIS KECAMATAN TANJUNG MORAWA - Safitri, Sakinah; Sutarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The objective of this research was to determine the cognitive learning outcomes of students using the Problem Based Learning model in the IPAS subject for fourth-grade students at SDN 101883 Limau Manis, Tanjung Morawa District. This research was classroom action research (CAR) consisting of three cycles, with two meetings in each cycle. Each cycle included four stages: planning, implementation, observation, and reflection. The subjects of this research were fourth-grade students at SDN 101883 Limau Manis, Tanjung Morawa District. This research utilized data collection techniques such as tests and non-tests, including observation, evaluation sheets, questionnaires, and documentation. The data analysis technique employed was quantitative analysis. The results indicated a significant improvement after using the Problem Based Learning model, as seen in the third cycle, where in two meetings, 18 students or 90% out of 20 students achieved mastery. This demonstrated that the students' learning outcomes reached the success indicator with a Minimum Completeness Criteria (KKM) of 70, achieving more than 70% in accordance with the provisions expected in the fourth grade at SDN 101883 Limau Manis, Tanjung Morawa District